Pengabdian Masyarakat oleh Mahasiswa (PMM) UMM Melalui Pendampingan Belajar pada Anak-anak TK Dharma Wanita Persatuan 1 Sengkaling - Indah Fajar Wati; Elvin Fitriyah; Hilya Asfara Mahila; Riq’atul Muniroh (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Community Service Activities by Students (PMM) Universitas Muhammadiyah Malang is a form of contribution in helping to solve problems that exist in society. This service mechanism is carried out by proposing, submitting permits for the place, preparing for service, implementing services, evaluating, and making reports. Learning assistance provided by students (PMM) Group 97 using the direct learning mentoring model at Dharma Wanita Persatuan 1 Sengkaling Kindergarten. This service aims to help teachers at the Dharma Wanita Persatuan 1 Sengkaling Kindergarten in the learning mentoring process. The activities carried out by the Group of 97 PMM UMM in learning assistance were learning calistung (reading, writing, counting), making crafts, and coloring competitions. These activities were supported and given a positive response by the teachers in the Dharma Wanita Persatuan 1 Sengkaling Kindergarten. The service activity ended with making window decorations for display in the children's classroom because the colors of the old decorations had faded so they had to be re-placed with new decorations. With the new decoration, it is hoped that the Dharma Wanita Persatuan 1 Sengka-ling Kindergarten children can be more cheerful and enthusiastic about learning.